To set up the distance formula to find the distance between points \( E \) and \( F \), you would use the standard distance formula:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Assuming that the coordinates of point \( E \) are \( (x_1, y_1) \) and the coordinates of point \( F \) are \( (x_2, y_2) \), you need to substitute the values accordingly.
If we take the responses you provided and assume:
- Point \( E \) has coordinates \( (-2, 5) \)
- Point \( F \) has coordinates \( (6, 1) \)
Using these points, the correct setup using the distance formula would be:
\[ d = \sqrt{(6 - (-2))^2 + (1 - 5)^2} \]
This simplifies to:
\[ d = \sqrt{(6 + 2)^2 + (1 - 5)^2} = \sqrt{(8)^2 + (-4)^2} = \sqrt{64 + 16} = \sqrt{80} \]
So the correct option from your list would be:
\[ d = \sqrt{(6 - (-2))^2 + (1 - 5)^2} \]
However, since you provided responses, the closest correct option matches with:
d = (6 - 2)^2 + (1 - 5)^2 (with appropriate values substituted in earlier contexts).
Make sure to clarify the exact coordinates of points \( E \) and \( F \) to validate completely.